Transparansi Dan Akuntabilitas Dalam Pelaporan Keuangan Syariah; Studi Pada Lembaga Keuangan Islam Di Indonesia - Wahyuni, Wahyuni; Yashari Soumena, Fadly (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to analyze the level of transparency and accountability in financial reporting at Islamic Financial Institutions (LKI) in Indonesia. Transparency and accountability are fundamental principles in Islamic finance to build stakeholder trust. This study explores how LKI's financial reporting practices in Indonesia implement these principles, including disclosure of financial and non-financial information, compliance with sharia accounting standards, and accountability mechanisms to stakeholders. The research method used is a qualitative descriptive approach with case studies on several LKIs in Indonesia. Data was collected through in-depth interviews with LKI management and analysis of financial statement documents. The results of the study are expected to provide a comprehensive overview of the challenges and opportunities in increasing transparency and accountability of Islamic financial reporting in Indonesia. The implications of this study are expected to contribute to the development of better Islamic financial reporting regulations and practices, thereby increasing trust and growth of the Islamic financial sector in Indonesia. Â